Some properties of water-clay dispersions and their effects on flow and sand transport phenomena - Haushild, W. L., author; Simons, Daryl B., author; Richardson, E. V. (Everett V.), 1924-, author; Colorado State University, U.S. Geological Survey, publisher (Colorado State University. Libraries, 1961)
Fine sediments dispersed in water affect the apparent viscosity and specific weight of the resulting dispersion. Tests at 24 degrees centigrade with a Stormer viscosimeter showed that the apparent kinematic viscosity for a 10 percent by weight water-clay dispersion of an impure bentonite was 8.75 times greater than that of distilled water. A 10 percent water-kaolin dispersion was 1.40 times more viscous than distilled water. The change in viscosity and density of the water-fine sediment dispersion changes the fall velocity of the bed material. The fall velocity distribution of the bed material can be determined, as a first approximation, with the visual accumulation tube apparatus when water-clay dispersions are the sedimentation media. The results are comparable to the fall velocities computed by using the Reynolds number-drag relation, the measured viscosity of the water-clay dispersion and the density of the dispersion. Experiments conducted in water- sand flows with and without bentonite in the flumes at Colorado State University demonstrated that with bentonite in the flow the changes in fall velocity of the bed material particles, resulting from the changes in fluid properties, altered the bed configuration. Because the resistance to flow and bed-material transport are dependent on the form of the bed, they were appreciably affected. Generally, as concentration of fine sediment increases with a constant rate of stream flow, flow resistance and transport of bed material always increase in the upper flow regime and sometimes decrease in the lower flow regime.
Some properties of water clay dispersions and their effect on flow
CER61WLH62.
Keywords: Sediment transport; Sand -- Transportation; Stream measurements; Fluid dynamics